Rpb5, a subunit shared by eukaryotic RNA polymerases, cooperates with prefoldin-like Bud27/URI - Verónica Martínez-Fernández; Francisco Navarro (AIMS Genetics, 2018)
Rpb5 is one of the five common subunits to all eukaryotic RNA polymerases, which is conserved in archaea, but not in bacteria. Among these common subunits, it is the only one that is not interchangeable between yeasts and humans, and accounts for the functional incompatibility of yeast and human subunits. Rpb5 has been proposed to contribute to the gene-specific activation of RNA pol II, notably during the infectious cycle of the hepatitis B virus, and also to participate in general transcription mediated by all eukaryotic RNA pol. The structural analysis of Rpb5 and its interaction with different transcription factors, regulators and DNA, accounts for Rpb5 being necessary to maintain the correct conformation of the shelf module of RNA pol II, which favors the proper organization of the transcription bubble and the clamp closure of the enzyme. In this work we provide details about subunit Rpb5’s structure, conservation and the role it plays in transcription regulation by analyzing the different interactions with several factors, as well as its participation in the assembly of the three RNA pols, in cooperation with prefoldin-like Bud27/URI.